Rekayasa SmartHome System Berbasis Internet of Things - Zulkarnaen, Muhammad Fauzi; Aliy Nauval Hanafi; Mohammad Taufan Asri Zaen (Fakultas Teknik Universitas Hamzanwadi, 2024)
In the current digital era, the Internet of Things (IoT) has emerged as a concept that presents new opportunities to expand sustainable internet connectivity. In the context of Smarthome, IoT enables the control of electronic devices through smartphone applications using internet connectivity, bringing various benefits, including increased comfort, enhanced security, better electricity savings, and introducing innovative solutions that not only allow real-time monitoring of home environments but also provide accessibility by considering the needs and preferences of various users, including families, busy individuals, and people with disabilities. The implementation of an IoT-based Smarthome system utilizes NodeMCU 8266 as a microcontroller, MIT App Inventor as a control tool, Thingspeak as a data processing platform, ESP32-CAM as a camera, and Telegram bot as a notification sender. This system includes the control of lights, fan, environmental monitoring, motion detection, gas leak detection, and fire detection. Various sensors are used, including Flame sensors for fire detection, MQ5 sensors for gas leak detection, and light sensors for automatically turning on lights. Relays are also applied to connect electronic devices to the system. Testing and system analysis show that equipment control operates according to the given commands, provided that the internet connection remains stable and continuous. This underscores the importance of a reliable network infrastructure in supporting the smooth operation of IoT-based Smarthome systems.